The Effectiveness of Assertive Skill Training to Improve Assertive Behaviour of Bullying Victims Students in Senior High School - Karyanti Karyanti (Jurnal Pendidikan Humaniora, 2015)
Keefektifan Pelatihan Keterampilan Asertif Untuk Meningkatkan Perilaku Asertif Siswa Korban Bullying di SMA